Pretreatment expression of miR-191a may predict response to the induction chemotherapy based on cytarabine in acute myeloid leukemia patients – a single-center pilotal study - Agnieszka Szymczyk; Sylwia Chocholska; Katarzyna Radko; Marek Hus; Monika Podhorecka (PLoS ONE, 2025)
Background Acute myeloid leukemia (AML) is associated with the accumulation of acquired genetic disorders. Moreorver chromosomal and molecular changes are independent prognostic factors that are taken into account to determine prognosis and treatment. MicroRNAs are novel gene regulators, which have been recognized to play an important role in pathological leukemogenesis. This study is aimed to analyze the possible role of micro RNAs as a markers predicting the outcome to induction chemotherapy based on cytarabine. Materials and methods The expression of miR-34a, miR-191, miR-199a and miR-199b in previously separated bone marrow cells was assessed at the moment of diagnosis in 44 AML patients with use of qRQ-PCR technique. Assessment of response to induction therapy was based on criteria for response to treatment proposed by European LeukemiaNet (ELN). Results Only the expression level of miR-191a out of all analyzed microRNAs was significantly associated with the induction chemotherapy response. We detected also significantly higher expression of miR-191 in FLT3-ITD negative group in comparison to FLT3-ITD positive subjects. For miR-34a, miR-199a and miR-199b, no relationship was found between their expression and FLT3-ITD, NPM1 and CEBPA mutations. It was also shown that in the group of patients with low miR-191 expression, the number of myeloblasts was higher (p < 0.05). Conclusions These results may prove an important role of miR-191a expression as a predictor of response to the induction chemotherapy based on cytarabine, even in cases when other risk factors are absent.